A Randomized Controlled Trial to Determine the Effect of Inhaled Corticosteroid on Intraocular Pressure in Open-Angle Glaucoma and Ocular Hypertension: The ICOUGH Study. Issue 2 (February 2017) - Moss, Edward B.; Buys, Yvonne M.; Low, Stephanie A.; Yuen, Darana; Jin, Ya-ping; Chapman, Kenneth R.; Trope, Graham E.
Abstract : Purpose: The purpose of this study was to determine the risk of a steroid pressure response from inhaled corticosteroids. Patients and Methods: This randomized, double-masked, placebo-controlled trial included 22 adults with well-controlled open-angle glaucoma or ocular hypertension. Consenting participants were randomized to a 6-week course of twice-daily fluticasone propionate 250-μg metered-dose inhaler or saline placebo metered-dose inhaler. Biweekly clinic visits included masked Goldmann applanation tonometry and assessment to identify adverse effects. Primary outcome was mean intraocular pressure (IOP) at week 6. Secondary outcomes included IOP elevation of >20% at 2 consecutive visits, adherence, side effects, and logMAR visual acuity. Results: A total of 10 patients in each arm completed the study. There were no statistically significant differences in IOP between groups at baseline (14.3±3.0 and 15.6±3.6 mm Hg in steroid and placebo groups, respectively, P =0.39) or at week 6 (14.7±2.4 and 14.8±3.8 mm Hg in steroid and placebo groups, respectively, P =0.92). Adherence was >80% for all participants. There were no statistically significant differences between groups in any secondary measures. One patient in the steroid group met the secondary end point of >20% elevation in IOP (IOP increased from baseline of 9 to 11 mm Hg at weeks 2 and 4). Conclusions: We found no clinically significant increase in mean IOP in patients with well-controlled open-angle glaucoma and ocular hypertension after 6 weeks of twice-daily inhaled fluticasone propionate compared with inhaled placebo. No participants exceeded their individualized target IOP. There were no differences in secondary outcomes.